Towards an inclusive social and emotional learning - Christina Cipriano; Michael F. McCarthy (Social and Emotional Learning: Research, Practice, and Policy)
Understanding the effectiveness of universal school-based SEL interventions for minoritized students in K-12 settings is an area of critical inquiry. In this paper, we draw on the evidence compiled from a recent systematic review and meta-analysis of thirteen years of universal school-based (USB) social and emotional learning (SEL) interventions for students in K-12 settings. Results simultaneously revealed that the field of SEL knows a great deal about the variation in effects of SEL programs and very little about the experiences of students with marginalized and minoritized identities within them. This manuscript details key findings and critical areas for future development in the service of gender-, racially-, ethnically-, linguistically-, and ability-minoritized youth. We begin with outlining what USB SEL interventions are and the evidence for them. We next discuss who marginalized and minoritized students are and the evidence of SEL programs effectiveness for them. We then discuss the urgent need for the SEL field to focus on program design, implementation, and research to better determine whether and how marginalized and minoritized students are benefiting from current USB SEL programming. Finally, we provide recommendations for improved research and practice to support a truly inclusive SEL hereafter. Impact Statement: This manuscript details critical developments in the service of SEL that benefits marginalized youth.